LOCATION AND QUANTITATIVE ANALYSIS OF OH IN COESITE - Koch-Muller M.; Fei Y.; Hauri E.; Liu Z. (My University, 2001)
The incorporation of hydrogen (deuterium) into the coesite structure was investigated at pressures from 3.1 to 7.5 GPa and temperatures of 700, 800, and 1100 °C. Hydrogen could only be incorporated into the coesite structure at pressures greater 5.0 GPa and 1100 °C . No correlation between the concentration of trace elements such as Al and B and the hydrogen content was observed based on ion probe analysis (1335 ± 16 H ppm and 17 ± 1 Al ppm at 7.5 GPa, 1100 °C). The FTIR spectra show three relatively intense bands at 3575, 3516, and 3459 cm-1font face=symbol>n1 ν3espectively) and two very weak bands at 3296 and 3210 cm-1font face=symbol>n4d ν5espectively). The band at 3516 cm-1 strongly asymmetric and can be resolved into two bands, 3528 (ν2and 3508 (ν2bm-1ith nearly identical areas. Polarized infrared absorption spectra of coesite single-crystal slabs, cut parallel to (0 1 0) and (1 0 0), were collected to locate the OH dipoles in the structure and to calibrate the IR spectroscopy for quantitative analysis of OH in coesite (εi5>,tot0 000 ± 30 000 l mol-1F>H2 cm-2).The polarized spectra revealed a strong pleochroism of the OH bands. High-pressure FTIR spectra at pressures up to 8 GPa were performed in a diamond-anvil cell to gain further insight into incorporation mechanism of OH in coesite. The peak positions of the ν1font face=symbol>n2nd ν3nds decrease linearly with pressure. The mode Gruneisen parameters for ν1font face=symbol>n2nd ν3e -0.074, -0.144 and -0.398, respectively. There is a linear increase of the pressure derivatives with band position which follows the trend proposed by Hofmeister et al. (1999). The full widths at half maximum (FWHM) of the ν1font face=symbol>n2nd ν3nds increase from 35, 21, and 28 cm-1 the spectra at ambient conditions to 71, 68, and 105 in the 8 GPa spectra, respectively. On the basis of these results, a model for the incorporation of hydrogen in coesite was developed: the OH defects are introduced into the structure by the substitution Si4+(Si2)2-[4]#(Si2)4OH-hich gives rise to four vibrations, ν1font face=symbol>n2afont face=symbol>n2bnd ν3ecause the OH(D)-bearing samples do contain traces of Al and B, the bands ν4d ν5y be coupled to Al and/or B substitution.
Keywords: COESITE; OH GROUPS; POLARIZED FTIR SPECTROSCOPY; HIGH-PRESSURE FTIR SPECTROSCOPY; ABSORPTION COEFFICIENT; ION PROBE ANALYSIS